The meaning of the two realities is knowledge, knowledge and resources in the Qur’an - Abdul Rahman, Ihsan Hassan Saleh (Arab Journal for Sciences and Research Publishing, 2020)
Meanings basis Arabic grammar. The significance of the acts "science" and "knew" and their resources in the Koran Grammatical semantic study This study aimed to draw attention، To be concerned with meanings، Because of their impact on understanding the Arabic sentence And because the Arabs are more eloquent than words She was able to express the meaning of interpretation of meaning The vocabulary of the Koran is his soul As well as to indicate the relationship of words among them And what they speak of common, synonymous, and contrasting and the observation of the word from the fact that it is a single, to the fact that it is a word And to clarify their significance in the context of the sentence contained therein. and support the callers to study the Koranic language absorbed to its vocabulary. to attempt to present its cognitive, scientific and global methodology. And the enumeration of the words "science" and "custom" in the Holy Quran. It also helps to understand vocabulary and understand its position in the sentence in terms of pronunciation. And its development on the level of significance important result is that science is divided into two parts: the perception of the same thing and this goes beyond the effect of one, and has nothing to do with "knew" and the second sentence.